2020
DOI: 10.1016/j.advms.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound in the diagnosis of COVID-19 infection - A case series and review of the literature

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Point‐of‐care ultrasound (POCUS) has been considered as a safe and effective bedside option in the initial evaluation, management, and monitoring of disease progression in patients with confirmed or suspected COVID‐19 infection 46 . A review from Buda et al 47 showed that POCUS could be considered for patients with suspected COVID‐19 whose PCR test result is negative. Besides, ultrasound examination may be worth considering because of its convenience, low cost, and safety (compares with CT scanning).…”
Section: Discussionmentioning
confidence: 99%
“…Point‐of‐care ultrasound (POCUS) has been considered as a safe and effective bedside option in the initial evaluation, management, and monitoring of disease progression in patients with confirmed or suspected COVID‐19 infection 46 . A review from Buda et al 47 showed that POCUS could be considered for patients with suspected COVID‐19 whose PCR test result is negative. Besides, ultrasound examination may be worth considering because of its convenience, low cost, and safety (compares with CT scanning).…”
Section: Discussionmentioning
confidence: 99%
“…Chest x-ray to detect lung involvement has low sensitivity, and CT chest should be considered when there is a respiratory compromise. 50,51 However, in the COVID-19 pandemic, the use of ultrasound for the detection of viral pneumonia has gained significant popularity and may detect changes earlier than a routine chest X-ray. 52…”
Section: Radiologymentioning
confidence: 99%
“…Lung ultrasound is emerging as a promising point-of-care tool to diagnose COVID-19 and efforts to standardize the use of this modality have come forth ( 13 ). Although it has several advantages compared to CT scans including the absence of radiation, lower cost, portability, and lower contamination risk, perhaps the most significant challenge with the use of lung ultrasound remains to be its potential for subjectivity and its reliance on the experience and expertise of the sonographer ( 14 , 15 ). In resource-constrained settings where trained personnel are not readily available, treatment decision-making and resource allocation may need to rely on more objective bases for the diagnosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%